Serum calprotectin: a potential biomarker to diagnose chronic prosthetic joint infection after total hip or knee arthroplasty - Thomas Ackmann; Jan Schwarze; Georg Gosheger; Tom Schmidt-Braekling; Jan Puetzler; Burkhard Moellenbeck; Christoph Theil (Scientific Reports, 2022)
Abstract The preoperative detection of prosthetic joint infection (PJI) prior to revision of total hip or knee arthroplasty is still a challenge. Serum Calprotectin (CP) is a heterodimer of two calcium-binding proteins present in the cytoplasm of neutrophils that is released in inflammatory processes and infections. The objective of this study is to determine the reliability of serum CP in the diagnosis of chronic PJI. 81 patients (40 women, 41 men) that presented a potential indication for revision arthroplasty of the hip (THA; n = 18) or knee (TKA, n = 63) at a single institution were prospectively evaluated. The joints were diagnosed as chronically infected or aseptic based on the musculoskeletal infection society (MSIS) criteria of 2018. Receiver operating characteristics and the Youden’s index were used to define an ideal cutoff value. The median serum CP level was significantly higher in the group with chronic PJI (15,120 vs. 4980 ng/ml; p < 0.001) compared to the aseptic cases. The calculated optimal cut-off value was 9910 ng/ml (AUC 0.899, 95% CI 0.830–0.968) with a specificity of 91% and sensitivity of 81%. The present investigation suggests that serum CP has a high specificity and good sensitivity to diagnose chronic PJI after TJA of the knee or hip.